Crescimento econômico e a associaç\~ao espacial de clusters municipais no Estado de Goiás: 2002-2016 - Antonio Marcos de Queiroz; Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The objective is to analyze the economic growth of the municipalities in Goiás, in the years 2002, 2010 and 2016, observing the dependence and spatial association in such municipalities. The methodology contemplates the use of spatial statistics, specifically the identification of spatial data autocorrelation, as well as the formation of spatial municipal clusters. The results show that in the high-high/low-low clusters are the municipalities with GDP growth per capita higher/lower than the state average. These clusters are located in the microregions of the Southwest of Goiás, Meia Ponte, Vale do Rio dos Bois and Catal\~ao (high-high clusters); and in the microregions of Porangatu, Surroundings of Brasília, Ceres, V\~ao do Paran\~a and Chapada do Veadeiros (low-low clusters). It is concluded that there is a very uneven and heterogeneous pattern in time and in the spatial distribution of economic growth in Goiás and that the spatial identification of clusters with a lower GDP growth rate per capita allows the elaboration of public policies so that the State can attract new investments in an attempt to mitigate regional inequalities and boost low growth municipalities.
Keywords: R12; 330; economic growth; spatial association; municipal clusters; Goiás